Mısır’ın İngiltere tarafından işgali ve Osmanlı Devleti’nin diplomasi mücadelesi: 1882-1887 - Kızıltoprak, Süleyman (My University, 2001)
Osmanlı Devleti, önemli eyaletlerinden biri olan Mısır'ın işgal edilmesi sürecinde, çok dikkatli bir politika izleyerek egemenlik haklarını korumaya çalıştı. Bu sırada, Osmanlı Devleti'nin dış politikasını elinde tutan II. Abdülhamid'in öncelik verdiği alan, Avrupa'nın yayılmacı tavırları karşısında, Osmanlı Devleti'nin siyasal bağımsızlığını ve toprak bütünlüğünü korumaktı. Bu bağlamda İngiltere'nin Mısır'ı işgal etmesi sürecinde, II. Abdülhamid tarafından belirlenen Osmanlı Devleti'nin dış politikası iki ayrı devrede gelişmiştir. İlk dönemde, Osmanlı Devleti tarafından belirlenen siyasetin hedefi, bir iç mesele olarak gördükleri Mısır sorununu yabancıların müdahalesine meydan vermeden ama, onlarla uzlaşarak ve buradaki çıkarlarını garanti altına alarak çözmekti. İlk olarak, İskenderiye'nin bombalanmasından önce, Abdülhamid'in izlediği siyaset, bir iç sorun olarak gördüğü Mısır krizine kendi başına çözüm bulmak ve yabancı güçlerin bu konudaki müdahale girişimlerine engel olmaya çalışmaktır. Ali Nizami Paşa ve Derviş Paşa heyetleri bu amaçla Mısır'a gönderilmiştir. İstanbul Konferansı sırasında izlenen siyaset de yabancıların Mısır sorununa karışmalarını engellemekti. Fakat, bu teşebbüsler, İngiltere'nin Mısır'ı işgal etmesine engel olamamıştır. İkinci dönemde, işgalden sonra izlenen politikalarda ise, Osmanlı Devleti'nin temel amacı İngiliz askerlerinin Mısır'daki işgaline son vermekti. Bunun için, Osmanlı devlet adamları çok yerinde bir strateji belirleyerek, işgali sona erdirecek bir takvim belirlenmesini, tüm diplomatik görüşmelerde, ısrarla talep ettiler. Hasan Fehmi Paşa, Londra'daki diplomatik görüşmelerden bir sonuç alamadan geri döndü. Wolff'un İstanbul görüşmeleri sırasında, Osmanlı görüşmecilerinin ortaya çıkan anlaşma metinleri için gösterdikleri titizlikler, dikkati çeken bir durumdur. Ancak gösterilen bu dikkatli çalışmalara rağmen, Wolff'un birinci İstanbul temaslarından sonra, diğer devletleri dışarıda bırakarak sorunu bir Osmanlı-İngiliz Sorunu olarak kabul ettirmekte başarı sağlayıp İngiltere'nin çıkarlarını gerçekleştirdiğini görmekteyiz. 24 Ekim 1885 Andlaşmasından kazançlı çıkan taraf, İngiltere olmuştur. Anlaşmayı imzalamakla İngiltere'nin Mısır'daki varlığını resmen tanıyan Padişahın Mısır üzerindeki egemenlik hakları önemli bir darbe yedi. Özellikle, İngiltere tarafından Mısır'a bir yüksek komiser tayin edilmesi, İngiltere'nin Mısır'ı işgal etmesini meşrulaştıran önemli bir madde idi. Mısır Yüksek Komiseri Gazi Ahmet Muhtar Paşa'nın Mısır'daki görevi sırasında, ciddi eleştirileri ve gayretli çalışmaları da Wolff'un görüşmelerdeki inatçı ve uzlaşmaz tutumunu engelleyememiştir. Bu doğrultudaki tavırlarını sürdüren Wolff'un 1887 yılında İstanbul'da ikinci kez yaptığı görüşmelerden bir sonuç alınamaması sürpriz değildir. Abdülhamid, Rusya ve Fransa'nın tehditleri ile İngiltere'nin baskıları arasında, zor bir karar vererek 22 Mayıs 1887 Andlaşma metnini imzalamamıştır. Bundan sonra İngiltere, Mısır'da Osmanlı Devleti'nin egemenliğini tanımaya devam etmiştir. Mısır'ı himaye altına almak ya da sömürgeleri arasına katmak, gibi bir politika izlemeye cesaret edememiştir. II. Abdülhamid bu iki ihtimalin İngiltere tarafından gerçekleştirilmesinin güç olacağını tahmin ederek anlaşma metnini imzalamadı. İngiltere'nin bu cesareti göstermesi 1914 yılına yani, I. Dünya Savaşı'nın başladığı zamana kadar ertelenmiştir. Dolayısıyla, 1882-1887 yılında uygulanan politikalar sayesinde, Osmanlı Devleti Mısır'da İngiltere'nin rahat hareket etmesini ve sömürge politikaları uygulamasını sınırlamıştır. Ayrıca, bu tecrübeden yola çıkarak Osmanlı Devleti'nin dış politikada, özellikle Abdülhamid'in padişahlığının ilk yıllarında uygulanan siyaseti şu şekilde tanımlamak mümkündür: Osmanlı politikası, riskten kaçınan, büyük devletlerle özellikle İngiltere ile savaşa yol açacak teşebbüslerden uzak duran, büyük devletlerle ilgili sorunlarını çözmek için bir başka güçten yardım alma arayışlarına giren, görüşme masasında tezlerini ifade ederken buyurgan ve otoriter değil, ikna edici yaklaşımlarda bulunan ve şartların değişmesini beklerken zaman kazanma politikasına sıkça başvuran ama, gücünün sınırlarının farkında olan özelliklere sahipti. Bu özelliklere sahip Osmanlı Devleti dış politika mekanizması, İngiltere'nin Mısır'dan çıkması için elinden gelenleri yapmıştır. Fakat, tahliye konusunda sonuç alamamıştır. Bununla birlikte, İngiltere'nin Mısır'da rahat bir şekilde istediğini yapmasına da izin vermemiştir. Mısır sorunu konusunda, Osmanlı Devleti'nin içinde bulunduğu iç ve dış şartlar, uluslararası alandaki gelişmeler ve Mısır'daki olaylar dikkate alınarak bir analiz yapıldığında, Osmanlı Devleti, Mısır üzerindeki egemenlik haklarını korumak için elinden geleni yapmıştır. Mısır sorunu konusunda belirlenen strateji; Osmanlı askeri müdahalesi olmadan İngiltere'yi Mısır'dan çıkarmaktı Bu strateji doğrultusunda uygulanan, her diplomatik zeminde tahliye maddesini gündeme taşımak ve tahliye konusunda verdiği sözler sebebiyle, İngiltere'yi büyük devletlere karşı sıkıştırmaya çalışmak gibi politikalar, genellikle doğru ve isabetli olmuştur. Ancak diplomatik alanlarda kullanılan araçlar tam bir etkinlik gösterememiştir. Diplomatik misyonların başarısızlıklarına yol açan en önemli faktörler arasında, yetişmişlik ve diplomatik tecrübe eksikliği bulunmaktadır. Son olarak Osmanlı Devleti, politika araçlarındaki zaafa ve dış politika önceliklerine rağmen, fiilen işgal altında bulunan Mısır üzerindeki haklarını, uzun süre korumayı başarmıştır. Dolayısıyla, belirlenen doğru strateji ve politikalar nedeniyle, Osmanlı Devleti İngiltere karşısında, Mısır'ı kolay bir lokma yapmamıştır. Kendi çıkarlarını korumak için, diplomasiyi etkin bir şekilde kullanmıştır. Diplomatik misyonların başarısız olmasına rağmen, etkin bir dış politika stratejisi belirleme konusunda, başarı sağlanmıştır. CONTENTS In the introduction part, to draw a complete picture of the problem the researcher explained the situation of the Egypt before the British occupation. At this point the most important question is, what was the suzerainty of the Ottoman Empire over Egypt before and after the French occupation? Besides this, the researcher tried to point out the historical perspective on the importance of Egypt in the 19th century and the decentralisation attempts of Egyptian governors after M. Ali Paşa. In the first part, the researcher focused on the reasons of the British occupation. Khidive Ismail Paşa's new attempts, financial crisis has been discussed in this part. As it is known Urabi revolt, which was a resistance against the dual control was also the main reason for the occupation. The issue have been written using the official documents and secondary sources. Attempts of the Sublime Porte to overcome the problem-in other words, Ali Nizami and Derviş Paşa comittee's missions has been explained in the second part. The Istanbul Conference which is held by the attempts of France to solve the Egyptian Question, has been discussed. Despite this Conference, how did Briton invade Egypt? What was the Urabi Movement according to Ottomans? The researcher tried to find some answers to these questions in this part. In the Part II, the researcher also, criticises the Ottoman Policy about the invasion of Egypt. In this part the researcher focuses on foreign policy decision makers and foreign policy applicators' achievements and failures. However, Abdülhamid's approach to the problem has been criticised. This part also have been written down from the first hand sources. Part three, operates as a pattern for criticising Ottoman diplomatic executions to overcome the Egyptian Question. The Agreement of 24 October 1885 and Mission of Sir Henry Drummund Wolf and Gazi Ahmet Muhtar Paşa as the extra-ordinary Consule-Generals has been explained depending on the first hand sources. Diplomatic activities of Hasan Fehmi Paşa in London has been discussed by the researcher. Besides this, The Agreement of 22 May 1887 and the reaction of Russia and France have been criticised using archival sources. Finally, in the last part, it is discussed the Great Powers' policies related to the Egyptian Question before and after British occupation.

OF THE RESEARCH The succersors of Muhammed Ali especially Ismail Paşa, were always eager to preserve and, if possible, to increase the degree of independence with Egypt had reached within the Ottoman Empire. During Ismail Paşa's reign The Ottoman Sultan gave him some privileges. These developments contributed to lose central power of the Ottoman Empire in Egypt. Therefore, the Ottoman Empire was conscious the restrictions of her power. She spent all energy to protect status-quo in Egypt. She gave more importance her suzerainty over Egypt. On the other hand she was very careful she may face with bigger trouble while considering overcome the Egyptian Problem. Cautious policies were put into practice to protect and continue her suzerainty. In January 1881 discontent among Egyptian officers arose again, as the Turco-Circassian minister of war had retired many of them while sparing those of his own ilk. Tevfik Pasha was indeed forced to exchange the minister for one acceptable to the Egyptians, Mahmud Sami al-Barudi. The officers' movement, whose leadership was taken by colonel Ahmed Urâbî, then gained strength by forming an alliance with the rural notables led by Muhammed Sultan Pasha. On 9 September a military demonstration in front of Khedive's palace in Cairo obtained the dismissal of Riyâd Pasha, the formation of a new government under Muhammed Sherif Pasha. In the election of the new chamber, Muhammed Sultan became its president. Britain and France, who had been following the rise of the national movement in Egypt with misgivings, on 8 January 1882 had begun a policy of open intervention by proclaiming, in identical notes presented to the Khedive, that they intended to support him and maintain the existing system of financial control. On 15 May they announced the imminent arrival of a combined naval sguadron in Alexandria. On 25 May they demanded the resignation of al-Bârûdî's ministry and Urâbî's banisment from Egypt. The ministry resigned but Urâbî protect his position as minister of war. On 11 June there was an outbreak of popular violence in Alexandria. The violence stemmed from a quarrel between a Maltese and an Egyptian porter. When the Maltese killed the porter accidently, the movement could not be taken undercontrol. About 50 Europeans 150 Egyptians were killed, in spite of the presence of the English and French squadron. Meanwhile, international diplomacy leading by France intervened the Egyptian problem. On 23 June, a conference of powers, opened at Istanbul. Sultan Abdulhamit was against this conference, but finally he accepted to the participation of it. He tried to use the chance for reinforcing his influence in Egypt. He send one of the most famous men, Derviş Pasha as an emissary. In the end, the decisive intervention fell upon Britain which, although with great reluctance on the part of the Gladstone government, wanted to prevent France from Egypt. So it acted on its own by having its ships bombard Alexandria on 11-12 July, on the pretext of keeping the Egyptians from further fortifying the harbour. When Tevfik Pasha now sought the protection of British troops in his palace in Alexandria, Urabi proclaimed himself responsible for the defence of the country, demanding that henceforth only his orders should be followed. The majority of the Egyptians supported the Urabi to fight against the domination of the foreigners. Tevfik Pasha and Derviş Pasha never succeded in controlling the movement. In August 1882 a British expeditionary corps occupied the Suez Canal. On 13 September 1882, British troops beat the Egyptian army at al-Tall al-Kabîr. Urabi and many participants of the movement were arrested. Urabi and other leaders of the movement were tried by military courts. Urabi was sentenced to death, but on British urging the sentence was commuted to exile. Did Urabi and his followers really want independence and to exercise power? They did not believe full independence was possible and so were willing to settle for something less. The effective aim of the movements which they started and led was not to drive the Ottoman ruler out, but to create a new balance between him and them. They would act as the notables had acted in the traditional system, as intermediaries between rulers and ruled, and would use their power to shift the balance in favour of local interests but would not try actively to destroy it completely. Britain had occupied Egypt, and Abdülhamit II had used diplomacy to prevent her. Probably he sensed there was nothing he could do. Britain needed to reassure the other Powers of her continuing respect for Egypt's legal status as a dependency of the Ottoman Empire, even while she was invading it. Egyptian Crisis arose at a particularly bad time for the Ottomans. The Empire was still bogged down in the consequences of the Turkish-Russo (Turco-Russian or Russo-Turkish) War of 1877-78 and the Congress of Berlin. The Empire was also being pressured by Russia to pay a very heavy war indemnity. Much of Ottoman financial self-control had been relinguished to the Ottoman Debt Comission in 1881. Moreover, in the same year Tunisia had been occupied by France. In other words during Egyptian Crisis Ottoman Empire had faced with many internal and external problems. Abdulhamid II, for his part, needed to do something to assert his sovereign rights, and perhaps, too, to assure Moslem opinion that he was making every effort to forestall the British occupation. Ottoman Empire needed an ally to solve the Egyptian question. Ideally, the solution to these problems lay in enlisting the support of a great Power protector. The difficulty was that, of the four possible protectors, Britain and Russia were unacceptable to the Sultan, France was unsafe and Germany was not interested. In the final analysis, Abdülhamid chose Britain because she was weaker: unlike Russia, she could not threaten him militarily, at least not directly, and the political threats she posed could be obtained through diplomacy and measures against internal subversion. Britain was the safer enemy. Successive attempts to bring the British to the negotiating table failed until December 1884, when they agreed to receive a special envoy from the Sultan. Hasan Fehmi Pasha, Ottoman minister of justice, was duly sent to London to secure a general settlement of the Egyptian question in accordance with Ottoman interests. His mission lasted form January until early May 1885, but failed to produce the desired settlement. And then Salisbury send Sir Henry Drummond Wolff to İstanbul to sign an aggrement. He was succesful in his first attempt but he failed in 22 May 1887. As a conclusion, Ottoman Diplomacy has made a great experience, during the negotiations. Especially Gazi Ahmet Muhtar Paşa, as a High-Comissioner in Cairo showed his diplomatic ability. As a result of the Ottoman policies, British administration in Egypt was not free of the some Ottoman obstacles. But this does not mean Ottoman diplomacy was successful because, they could not stop the occupation. On the other hand, British colonisation towards Egypt, were delayed by the Ottoman Empire.
Keywords: Mısır_Tarih; Siyasi Tarih_Osmanlı İmparatorluğu